2010
DOI: 10.1093/jjco/hyq146
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival and Updated Results from a Phase II Study of Sunitinib in Japanese Patients with Metastatic Renal Cell Carcinoma

Abstract: With the median overall survival benefit exceeding 2.5 years, and acceptable tolerability, in first-line and pretreated Japanese metastatic renal cell carcinoma patients with Eastern Cooperative Oncology Group performance status 0/1, sunitinib showed a favourable risk/benefit profile, similar to Western studies. However, there was a trend towards greater efficacy and more haematological adverse events in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
69
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 9 publications
19
69
7
Order By: Relevance
“…(3,4) In Japan, the MSKCC risk classification is widely used not only in clinical trials, but also in daily clinical practice. (5,6) However, whether this risk classification is useful for predicting outcomes in Japanese patients with metastatic RCC is not unclear. Recently, we performed a retrospective study on the MSKCC risk classification in patients with metastatic RCC and reported its applicability to Japanese patients.…”
mentioning
confidence: 99%
“…(3,4) In Japan, the MSKCC risk classification is widely used not only in clinical trials, but also in daily clinical practice. (5,6) However, whether this risk classification is useful for predicting outcomes in Japanese patients with metastatic RCC is not unclear. Recently, we performed a retrospective study on the MSKCC risk classification in patients with metastatic RCC and reported its applicability to Japanese patients.…”
mentioning
confidence: 99%
“…The updated efficacy and safety data in the present report confirmed that S-1 was effective in patients who had failed to respond to prior cytokine treatment, and no new safety-related findings were detected during .3 years from the interim analysis to the final data cutoff. We acknowledge that this is not a randomized study and the efficacy results of the final analysis should be considered as exploratory; however, it was encouraging that the median OS was 42.8 months and numerically longer when compared with those reported in Japanese studies of sorafenib (25.3 months) and sunitinib (32.5 months) (17,18). This study was initiated before the approval of TKIs and mammalian target of rapamycin inhibitors in Japan.…”
Section: Discussionmentioning
confidence: 95%
“…Hypothyroidism was also considered to be an important AE associated with sunitinib treatment, for which 31 patients (53.4%) required medication during this study. ficacy and safety of these agents in the Western world [7,8,11], only few reports have described findings in Asian populations [12][13][14]19]. In 2010, Tomita et al reported updated results from a Phase II trial of sunitinib in the Japanese population [14].…”
Section: Evaluation Of Aesmentioning
confidence: 99%
“…In addition, only patients with clear-cell histology were eligible for the study [8]. Although sunitinib has been universally prescribed to patients with mRCC, few studies have examined the efficacy and safety of this agent in daily clinical practice, especially in patients of Asian ethnicity [12][13][14][15]. Here, we assessed the efficacy and safety of sunitinib in Japanese patients with mRCC in general clinical practice.…”
Section: Introductionmentioning
confidence: 99%